Distributions of trace metals, chlorophyll-a and nutrients in Melaban and Sibu Laut Rivers, Sarawak - Nurnadhirah, Bt Mohd zaki (Universiti Malaysia Sarawak (UNIMAS), 2012)
The aim of this study was to understand the distributions of selected trace metals in the riverine waters. The concentrations of selected trace metals in the surface, middle and bottom of waters were collected from two rivers: Melaban (6 stations) and Sibu Laut (8 stations) Rivers. The selected trace metals: chromium (Cr), copper (Cu), iron (Fe), nickel (Ni), lead (Pb), and zinc (Zn) were determined by Atomic Adsorption Spectrophotometer (AAS). The concentrations of these elements in the Melaban River were Cr (3.4-41.7Ilg/L), Cu (0.3-8.31lg!L), Fe (43-259.80 IlgIL), Ni (0.3-2.60 1lg!L), Pb (6.7-11 IlgIL) and Zn (107-156.33Ilg/L). The concentrations of these elements in the Sibu Laut River were Cr (20.5-95.23 Ilg/L), Cu (0.8-7.8IlgIL), Fe (0.14-l4.9IlgIL), Ni (4.7-47.9IlgIL), Pb (0.4-17.53 1lg!L) and Zn (54.7-142 1lg/L).These high concentrations appear to be due to the anthropogenic load from nearby local activities. Results for levels in water were compared with national and international water quality guidelines, as well as literature data repon for the national rivers.